2010
DOI: 10.1039/b923970g
|View full text |Cite
|
Sign up to set email alerts
|

On-chip determination of spermatozoa concentration using electrical impedance measurements

Abstract: In this article we describe the development of a microfluidic chip to determine the concentration of spermatozoa in semen, which is a main quality parameter for the fertility of a man. A microfluidic glass-glass chip is used, consisting of a microchannel with a planar electrode pair that allows the detection of spermatozoa passing the electrodes using electrical impedance measurements. Cells other than spermatozoa in semen also cause a change in impedance when passing the electrodes, interfering with the sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 24 publications
0
62
0
Order By: Relevance
“…These observations strongly argue that the sperm genome provides an epigenetically poised set of developmental genes that potentially have a crucial effect on embryological growth and development. Although the recent development of microfluidic devices,27, 28, 29, 30, 31 to some extent, addressed these needs around motility and DNA fragmentation,32 majority of these devices require chemoattractants and pumps to provide the required flow conditions, causing undesirable sample dilution and presenting structural barriers for implementation at the clinic. In addition, they have fallen short of sorting for epigenetic aberrations ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…These observations strongly argue that the sperm genome provides an epigenetically poised set of developmental genes that potentially have a crucial effect on embryological growth and development. Although the recent development of microfluidic devices,27, 28, 29, 30, 31 to some extent, addressed these needs around motility and DNA fragmentation,32 majority of these devices require chemoattractants and pumps to provide the required flow conditions, causing undesirable sample dilution and presenting structural barriers for implementation at the clinic. In addition, they have fallen short of sorting for epigenetic aberrations ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…These microfluidic devices can be used by pipetting sample liquid without complex fluid manipulation systems, such as electric pumps and bulbs, leading to the advantages of simplicity and low cost. Since the 1990s, microfluidic devices for sperm counts and motility analyses have been investigated by Kricka et al [39], and microfluidic POC systems for semen diagnostics sorting motile sperms or on-chip IVF using LOC have been reported [40][41][42][43][44][45][46][47][48][49][50][51]. Moreover, in addition to motile sperm separation, fluid flow-and viscosity-associated chemotaxis and mechanotaxis of mammalian sperm were investigated using microfluidic channels [45].…”
Section: Microfluidic Channel-based Devices For Semen Diagnoses and Mmentioning
confidence: 99%
“…Within the last decade, studies using PDMS microfluidic channels or funnels have suggested novel solutions for oocyte manipulation, sperm sorting, and embryo culture . Microfluidic systems that mimic oviductal structures and functions for use in RT are divided into those used for sperm motility control or monitoring [50][51][52][53][54][55][56][57][58][59][60], regulation of chemical gradients for in vitro fertilization and embryo culture [61][62][63][64][65][66][67][68][69], and applying mechanical stimuli to the developing embryo [70][71][72][73][74]. Although the unique characteristics of elastomers have been exploited for microstructure fabrication and/or micro-pumping, mechanical deformation of the elastomer membrane has not been used to produce new devices for RT.…”
Section: Microfluidic Channels To Handle Sperm and Embryosmentioning
confidence: 99%
“…A minimal image platform is desired to enable compactness, ease-of-use, minimized footprint, and portability to monitor sperm motility by a preclinical assay at home. Some researchers have developed a microfluidic chip that can be used by an individual himself at home on convenient moments to check his semen quality [56][57][58][59]. For example, if a person finds that his semen quality is low or that there are no motile sperm in his semen, he can opt for ICSI for his fertility treatment.…”
Section: Elastomer Chip Device For Analyzing Motility Of Motile Spermmentioning
confidence: 99%